2015
DOI: 10.1080/10286020.2015.1055729
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral glycosidic bisindole alkaloids from the roots ofIsatis indigotica

Abstract: Seven new glycosidic bisindole alkaloids, isatindigobisindolosides A-G (1-7), were isolated from an aqueous extract of the Isatis indigotica roots. Their structures including absolute configurations were determined by spectroscopic and chemical methods, together with calculations of electronic circular dichroism (ECD) spectra based on the quantum-mechanical time-dependent density functional theory. In the NMR spectra of 1-3, it is found that integration of H-2 and intensity of C-2 are affected not only by a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…This was confirmed by a typical cyano absorption band at 2257 cm —1 in the IR spectrum of 6 , especially by the HMBC correlations from H-1 to C-2, C-3, C-3a, and C-7a; from H 2 -8 to C-2, C-3, C-3a, and C-9, and from OC H 3 to C-4. In addition, as compared with those of the previously isolated analogues from this extract37, 38, 39, 40, 41, 42, 43, 44, 45, the chemical shifts of C-2 ( δ C 139.0, deshielded) and C-3 ( δ C 99.8, shielded) supported location of the sulfonic acid unit. Therefore, the structure of compound 6 was determined as 3-(cyanomethyl)-4-methoxy-1 H -indole-2-sulfonic acid and named isatindosulfonic acid D.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…This was confirmed by a typical cyano absorption band at 2257 cm —1 in the IR spectrum of 6 , especially by the HMBC correlations from H-1 to C-2, C-3, C-3a, and C-7a; from H 2 -8 to C-2, C-3, C-3a, and C-9, and from OC H 3 to C-4. In addition, as compared with those of the previously isolated analogues from this extract37, 38, 39, 40, 41, 42, 43, 44, 45, the chemical shifts of C-2 ( δ C 139.0, deshielded) and C-3 ( δ C 99.8, shielded) supported location of the sulfonic acid unit. Therefore, the structure of compound 6 was determined as 3-(cyanomethyl)-4-methoxy-1 H -indole-2-sulfonic acid and named isatindosulfonic acid D.…”
Section: Resultsmentioning
confidence: 71%
“…for C 23 H 23 N 2 O 9 S, 503.1130) and NMR spectroscopic data. As compared with those of the previously isolated chemical constituents from the same extract37, 38, 39, 40, 41, 42, 43, 44, 45, the NMR spectroscopic data of 1 in CD 3 OD (Table 1) indicated the presence of one 2,3-disubstituted 1 H -indole ring, one 1′ H -indol-3′-yl, a β -glucopyranosyl, and an isolated methine. This, together with the molecular formula, indicated that 1 was an uncommon sulfur-containing bis(indolyl)methane β -glucopyranoside37, 40, 41, of which the planar structure was further elucidated by interpretation of 2D NMR spectroscopic data.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, an aqueous decoction of “ban lan gen” was investigated as part of our program to systematically study the chemical and biological diversity of several Chinese traditional medicines10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. From the decoction, 43 new alkaloids and 54 known compounds, including a pair of indole alkaloid enantiomers containing dihydrothiopyran and 1,2,4-thiadiazole rings, a pair of bisindole alkaloid enantiomers, four stereoisomers of 3,5-bis(2-hydroxybut-3-en-1-yl)-1,2,4-thiadiazole, and twelve glycosidic indole alkaloids, as well as their antiviral and/or hepatocyte-protective activities, were characterized23, 24, 25, 26, 27, 28, 29, 30. Continuous investigation on remaining fractions from the decoction resulted in the separation of a pair of unusual new diphenyl glycerol ether enantiomers (−)- 1 and (+)- 1 and two new methyl benzamidobenzoates ( 2 and 3 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%